164k views
3 votes
Simplify.
Rewrite the expression in the form y^n

Y^9•y^2

2 Answers

1 vote
Simply such an app I can put in app and I wanna is the best way app is to buy the best of it i will you have a good man is the day I can put i it in the same world I can put it
User Trista
by
5.5k points
3 votes

Answer:

Explanation:

When you multiply two terms with same base, add the exponents.

Example: x*x² = x* x*x = x³

In short, x*x² = x¹⁺² = x³


y^(9)*y^(2)=y^(9+2)\\\\ = y^(11)

User Murat
by
5.6k points